The urban drainage management practised by local authority / Mohd Nuralimin Johari - Johari, Mohd Nuralimin (Faculty of Architecture, Planning and Surveying, 2013)
Drainage system has been investigated in this thesis formation. As the title is drainage management practised by local authority, this thesis explains in detailed the types of drainage, their management regard to the issued and also their improvement ways to the drainage. To be full knowledge of the drainage management and the improvement ways, several case studies has been carried out at Selangor. Three local authorities have been selected to make a comparison between them. They are Majlis Bandaraya Shah Alam, Majlis Perbandaran Klang and Majlis Perbandaran Kajang. The drainage management and their improvements ways taken by local authority have been clarified in the chapter has been analysed by doing the semi structured interviewed among local authority and also observation at the selected area. The problems encounter also stated in the analysis. As the thesis has been completed, the drainage system at certain area are totally differs from other location because of their factors a lots of population in the residential area that influence the types of drainage systems.